ΕΣΧΑΡΑ. An etymological vexāta quaestiō of the Greek lexicon (Atti del Sodalizio Glottologico Milanese, 2017)
The paper explains the origin of the Greek lexeme ἐσχάρᾱ “hearth” from the point of view of various branches (archaeology, linguistics, anthropology) and looks into the cultural nature of the relevant referent. Besides it studies the lexicon pertinent to the basic notion of |INFLAMED WOOD| in Aryan, Slavonic, Latin, Germanic languages and identifies Hittite ēšḫar / išḫar “sacrificial blood” as the original paradigm for a loanword got into the Greek lexicon within the Micrasiatic area where a phenomenon of language alliance took origin (Gusmani). This work connects also the Greek lexematic series ἐσχάρᾱ, ἄδις, βόθρος, ἔαρ, αἷμα with the notions of |HOLLOW BRAZIER|, |SACRIFICAL BLOOD|, |VITAL LYMPH| and proves their considerable antiquity and partial survival up to now throught etymological paths. KEYWORDS: Indo-European, Greek, etymology, cultural reconstruction, lexicon